« Les concavités de la conscience » : l’hypotypose comme un lieu de persuasion dans la polémique autour de la conversion de Henri IV - Wawrzyniak, Natalia (Acta Universitatis Lodziensis. Folia Litteraria Romanica, 2018)
The conversion of Henry of Navarre in 1593 provoked a great debate in the French society. In The Banquet of Comte d’Arète (1594), Louis Dorléans focuses obsessively on the impenetrability of the human mind. He calls for a dissection of king’s consciousness in order to find traces of heresy : “let’s examine its concavities up to his deepest thoughts”. Monstrous anatomical details represent a “bad consciousness” of the king to arouse the disgust of the reader. The aim of this article is to analyse the practice of hypotyposis in this polemical text. The ekphrastic description of the human mind proves how vital the question of spiritual, emotional and mental transformation was at the time of religious wars. The use of hypotyposis illustrates as well one of the aporias of persuasion, namely the problem of authenticity. From rhetorical point of view, internal metamorphosis remains a mystery. How indeed one may judge the victory of the orator and decide about the sincerity of the change that has occurred?